2023
DOI: 10.1111/jne.13285
|View full text |Cite
|
Sign up to set email alerts
|

KNDyneurones andGnRH/LHpulse generation: Current understanding and future aspects

Abstract: Uncovering the central mechanism underlying mammalian reproduction is warranted to develop new therapeutic approaches for reproductive disorders in humans and domestic animals. The present study focused on the role of arcuate kisspeptin neurones (also known as KNDy neurones) as an intrinsic gonadotropin‐releasing hormone (GnRH) pulse generator, which plays a fundamental role in mammalian reproduction via the stimulation of pituitary gonadotropin synthesis and release and thereby in gametogenesis and steroidoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 231 publications
(376 reference statements)
0
7
0
Order By: Relevance
“…We did not observe alterations in gonadotropin expression in the pituitary gland, but we found a reduction in Tac2 levels, coding for Neurokinin B, in the hypothalamus of LepRb-cre ΔVglut2 females. These findings indicate that blockade of glutamatergic neurotransmission in LepRb neurons disrupts key components of the GnRH pulse generator (Han et al, 2023 ;Ruka et al, 2013 ;Uenoyama and Tsukamura, 2023 ), leading ultimately to reproductive deficits.…”
Section: Discussionmentioning
confidence: 93%
“…We did not observe alterations in gonadotropin expression in the pituitary gland, but we found a reduction in Tac2 levels, coding for Neurokinin B, in the hypothalamus of LepRb-cre ΔVglut2 females. These findings indicate that blockade of glutamatergic neurotransmission in LepRb neurons disrupts key components of the GnRH pulse generator (Han et al, 2023 ;Ruka et al, 2013 ;Uenoyama and Tsukamura, 2023 ), leading ultimately to reproductive deficits.…”
Section: Discussionmentioning
confidence: 93%
“…We did not observe alterations in gonadotropin expression in the pituitary gland, but we found a reduction in Tac2 levels, coding for Neurokinin B, in the hypothalamus of LepRb-cre Δ Vglut2 females. These findings indicate that blockade of glutamatergic neurotransmission in LepRb neurons disrupts key components of the GnRH pulse generator (Han et al, 2023; Ruka et al, 2013; Uenoyama and Tsukamura, 2023), leading ultimately to reproductive deficits.…”
Section: Discussionmentioning
confidence: 95%
“…We did not observe alterations in gonadotropin expression in the pituitary gland, but we found a reduction in Tac2 levels, coding for Neurokinin B (NKB), in the hypothalamus of LepRb-cre Δ Vglut2 females. These findings indicate that blockade of glutamatergic neurotransmission in LepRb neurons disrupts key components of the GnRH pulse generator (Han et al, 2023; Ruka et al, 2013; Uenoyama and Tsukamura, 2023), leading ultimately to reproductive deficits. Indeed, previous research showed that activation of the Neurokinin 3 receptor (NK3R) by an NKB agonist induced GnRH release consistently from the ME even in kisspeptin knockout animals, but not the preoptic region where GnRH cell bodies are located (Gaskins et al, 2013), suggesting that Tac2 alone could be a direct mediator of the glutamatergic effect on GnRH release.…”
Section: Discussionmentioning
confidence: 95%
“…The HPG axis, a neuroendocrine system, plays a role in reproduction by regulating LH/FSH and sex steroid secretion. The KNDy pathway is also linked to reproductive function [ 32 ]. In our research, we studied the genetics of the PDYN / OPRK1 complex; however, no mutations were found.…”
Section: Discussionmentioning
confidence: 99%